Porokeratosis. Case Presentation - Lino Sánchez Galbán; Damarys Díaz Leonard; Mery Rosa Betancourt Trujillo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Porokeratosis is an epidermal dermatosis characterized by single or multiple annular, keratotic and hyperpigmented lesions of chronic evolution. It is considered as a pre-malignant lesion with a high risk of epidermoid carcinoma production. A case of an 18-year-old patient, who, from the first months of life, presented skin lesions with linear distribution, disseminated on the face, trunk and both limbs, as well as some unyielding, hyperkeratotic-looking beds with walled edges and atrophic center of light brown color. In 2003 the histological diagnosis of porokeratosis was confirmed. This article describes the treatment and evolution of this patient, affected by a very rare disease, both in Cuba and worldwide.